Handbook on Digital Learning for K-12 Schools 2016
DOI: 10.1007/978-3-319-33808-8_22
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Computer-Assisted Language Learning in Saudi Schools: A Change Model

Abstract: Computer-assisted language learning (CALL) technology and pedagogy have gained recognition globally for their success in supporting second language acquisition (SLA). In Saudi Arabia, the government aims to provide most educational institutions with computers and networking for integrating CALL into classrooms. However, the recognition of CALL's efficacy does not translate into easy acceptance and integration in English as a Second Language or English as a Foreign Language (ESL/EFL) classrooms in Saudi schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…It enhances the language teaching and learning activities (Mahmood, Bokhari, & Naqvi, 2011) and improves the effectiveness of teaching and learning instruction (Lakshmi, 2012;Wu, Pan, & Yuan, 2016;Munir, 2016;Rakhmawati, 2016). It also fosters students' learning attitudes, including their enthusiasm (Isisag, 2012), interest (Al-Mohammadi & Derbel, 2014;Alresheed, Leask, & Raiker, 2015), and motivation (Al-Mohammadi & Derbel, 2014;Altun, 2015;Anikina, Sobinova, & Petrova, 2015) and also supports learning style diversity (Ezza & Bakry, 2014) for all students in the classroom. Furthermore, the existence of technology also helps the teacher in improving the teachers' teaching performance, including problem solving, classroom interaction, and teaching and learning activity design (Al-Maagbeh, 2015).…”
Section: Technology Integration In English Teaching and Learning Processmentioning
confidence: 99%
“…It enhances the language teaching and learning activities (Mahmood, Bokhari, & Naqvi, 2011) and improves the effectiveness of teaching and learning instruction (Lakshmi, 2012;Wu, Pan, & Yuan, 2016;Munir, 2016;Rakhmawati, 2016). It also fosters students' learning attitudes, including their enthusiasm (Isisag, 2012), interest (Al-Mohammadi & Derbel, 2014;Alresheed, Leask, & Raiker, 2015), and motivation (Al-Mohammadi & Derbel, 2014;Altun, 2015;Anikina, Sobinova, & Petrova, 2015) and also supports learning style diversity (Ezza & Bakry, 2014) for all students in the classroom. Furthermore, the existence of technology also helps the teacher in improving the teachers' teaching performance, including problem solving, classroom interaction, and teaching and learning activity design (Al-Maagbeh, 2015).…”
Section: Technology Integration In English Teaching and Learning Processmentioning
confidence: 99%
“…These studies have shown a significant effect of integrating technology in teaching English language on students' English proficiency levels and attitudes towards learning English (Al-Shehri, 2011, Al-Okaily, 2013, AlRowais, 2014, Al-Harbi, 2015, Al-Kathiri, 2015Alresheed, Leask, & Raiker, 2015, Al-Harbi & Alshumaimeri, 2016, Al-Otaibi, 2016Al-Zahrani, 2015).…”
Section: The Saudi Teaching Context and Flipped Classroommentioning
confidence: 99%
“…Murthy et al (2015) and Warriem et al (2014) build on this knowledge base with the A2I model (Attain-Align-Integrate). Similarly, the teacher's role in process innovation is analysed via the K20 model (WILLIAMS et al, 2008), the Teaching Development Programme model (TDP) (ALBION et al, 2015), the Concerns-Based Adoption Model (CBAM) (KARMESHU et al, 2013;PEARSON, 2015), and the Technology Acceptance model (ALRESHEED et al, 2015). Regarding the study of the dynamic relationships between learning agents and ICT, Toh 2016, Zagami (2013) and Lin (2011) used the ecological model as a reference point.…”
Section: Models For the Pedagogical Integration Of Information And Comentioning
confidence: 99%